Pengembangan Modul Fisika Berbasis Discovery Learning pada Materi Fluida Statis Siswa Kelas XI SMA Negeri 1 Lubuklinggau Tahun Pelajaran 2019/2020 - Nadia Apriyani; Tri Ariani; Wahyu Arini (LP4MK STKIP PGRI Lubuklinggau, 2020)
All The All objectives of the reserch was to develop the Physics module with discovery learning on Static Fluid Material that is valid, practical and effective. The subjects in this study were the entire class XI Natural Sciences and the broad group research subjects in this study were the XI MIPA 4 class of SMA Negeri 1 Lubuklinggau in the 2019/2020 Academic Year consisting of 36 students taken by simple random sampling technique. Data collection was carried out using questionnaire and test techniques. Validation is done to get results with a good category that is with a percentage of 78.81%. Student responses to the discovery learning based module were 88.25%. Besides that from the results of daily tests conducted, it was found that student learning outcomes were completed with an average of 83.8. As well as the average percentage of student activity at the time of practicum which is 71.4% included in both categories. The value of t table with degrees of freedom (dk) = n-1 = 36 ─ 1 = 35 and α = 0.05 tcount = 2.95 and ttable = 1.689 because tcount ≥ ttable then Ha is accepted. So it can be said that the Discovery Learning-based Module that was developed has been valid, practical, and effective.